2022
DOI: 10.1093/gastro/goac008
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring host–microbe interactions and barrier function during gastrointestinal inflammation

Abstract: Organismal survival depends on a well-balanced immune system and maintenance of host–microbe mutualism. The fine-tuned relationship between the gut microbiota and host immunity is constantly challenged by opportunistic bacteria testing the integrity of gastrointestinal (GI) barrier defenses. Barrier dysfunction reduces immunological tolerance towards otherwise innocuous microbes; it is a process that may instigate chronic inflammation. Paradoxically, sustained inflammation further diminishes barrier function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 188 publications
0
18
0
Order By: Relevance
“…Nevertheless, Eleftherios P Diamandis held that Prevotella copri proliferate in a specific dietary and lifestyle milieu are epiphenomena for a lifestyle ( 41 ). Enrichment of Prevotella copri is predictive for Western individuals responding favorably to a high-fiber, barley-kernel-based diet ( 42 ). These studies ( 41 , 42 ) indicated the influence of diet on the abundance and contrasting effect of Prevotella copri .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Eleftherios P Diamandis held that Prevotella copri proliferate in a specific dietary and lifestyle milieu are epiphenomena for a lifestyle ( 41 ). Enrichment of Prevotella copri is predictive for Western individuals responding favorably to a high-fiber, barley-kernel-based diet ( 42 ). These studies ( 41 , 42 ) indicated the influence of diet on the abundance and contrasting effect of Prevotella copri .…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of Prevotella copri is predictive for Western individuals responding favorably to a high-fiber, barley-kernel-based diet ( 42 ). These studies ( 41 , 42 ) indicated the influence of diet on the abundance and contrasting effect of Prevotella copri . Further mechanism study of Prevotella copri in relation to T1D is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of CD is not fully understood but it is thought to develop as a result of interactions between environmental, microbial, and immune-mediated factors in a genetically susceptible host (1). Gut dysbiosis has been observed in many gastrointestinal diseases (2)(3)(4)(5), including CD. An imbalance of microbiota may be an important indicator of the occurrence and development of CD (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the microbiota modulates the pathogenesis, progression, and treatment of various diseases, and modulating host-microbiota interactions is an emerging therapeutic avenue for disease control and prevention. This complex ecosystem is maintained with the interplay of nutrients, microbiota, and the host that is distinctive along the length of the intestine (1,2,9). The intestinal epithelial cells are located at the vital interface between microbiota/nutrients and the host and play a key role in the host-microbiota-nutrient interplay by functioning as a selective barrier that prevents the entry of harmful molecules while absorbing necessary nutrients (4,10).…”
Section: Introductionmentioning
confidence: 99%
“…This complex ecosystem is maintained with the interplay of nutrients, microbiota, and the host that is distinctive along the length of the intestine ( 1 , 2 , 9 ). The intestinal epithelial cells are located at the vital interface between microbiota/nutrients and the host and play a key role in the host-microbiota-nutrient interplay by functioning as a selective barrier that prevents the entry of harmful molecules while absorbing necessary nutrients ( 4 , 10 ).…”
Section: Introductionmentioning
confidence: 99%